Influence of the pressure of compacted glass powders on the final structure of sintered glass-ceramics - N.B. Jordanov; D. Tatchev; E. Karamanova; A. Karamanov (Heliyon)
In reported investigation we studied sintered glass-ceramics from a model diopside glass with moderate crystallization ability by in-situ optical dilatometeric experiments. The initial glass was ground and sieved below 75 μm. Then thus prepared powders were pressed with different pressures between 50 and 250 MPa. In this way were obtained samples out of pressed powders with different initial porosities determined with gas pycnometry. Then the samples were heat treated in a contactless horizontal optical dilatometer and their porosities were measured one more time. Both pressed green samples and synthesized glass-ceramics were analyzed further with X-Ray micro tomography.We observed that the densification of all samples completes in the same moment which corresponds to the formation of a critical percentage crystal phase. Notwithstanding the continuation of the crystallization process, we obtain materials with different percentage of residual porosity. Then no volume variation of the system is observed. This approach is well demonstrated by the first derivative of the shrinkage curves with time.After the end of the shrinkage of the system, the crystallization leads to the formation of crystallization induced porosity (called by us CIPs) observed here.